STUDI LITERATUR MEDIA PEMBELAJARAN YANG DIGUNAKAN PADA MODEL PEMBELAJARAN PROBLEM BASED LEARNING - Theo Artkin Sitorus; Nurhasanah Siregar (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2023)
This research aims to describe the analysis result of the use of learning media in the Problem Based Learning model. The methods used in this research is literature study of 6 sources consists of 3 thesis and 3 journals discuss the use of learning media in the Problem Based Learning model in Indonesia published in the span of 2016-2022. From the calculation of the effect size, the average value is 0.79 which is categorized in the medium category. This shows that the use of learning media with Problem Based Learning in mathematics learning had a positive effect on improving the mathematical ability of students and the effect obtained is in the medium category. The mathematical ability could be improved based on the literature study such as student’s mathematical connection ability, student’s mathematical problem soving ability dan student’s mathematical numeracy literacy ability. The type of learning media according this research are animation, geogebra, microsoft power point, fun math book, cabri 3D v2 dan youtube. Hope for further research can be analyzed more deeply by using more sources so the result will be more maximal and varied.